Self-transformation: Body, Mind, and Spirit - William Konchak (Journal of Applied Hermeneutics, 2017)
In this paper, I explore a conception of self-transformation that attempts to provide a holistic account covering a range of body, mind, and spirit.  I draw upon Kym Maclaren’s exploration of the role of the body inspired by the work of Maurice Merleau-Ponty (body); the hermeneutics of Hans-Georg Gadamer (mind [language]); and Ralph Waldo Emerson’s transcendentalism (spirit).  I present the case that each of these approaches develops important aspects of self-transformation and can be seen as complementary. I explore this in relation to philosophy as a practical activity, drawing upon Pierre Hadot’s perspective of philosophy as a way of life.